Negotiated power : the state, elites, and local governance in twelfth- to fourteenth-century China - Lee, Sukhee, 1971- (Harvard East Asian monographs, 2014)
"Posits an alternative understanding of the relationship between the state and social elites in the middle period of Chinese imperial history. The book shows in vivid detail how state power and local elite interests were mutually constitutive and reinforcing"--Provided by the publisher